Leaf anatomical features of three Theobroma species (Malvaceae s.l.) native to the Brazilian Amazon - Garcia,Tarcymara Barata (2014)
Theobroma species have economic importance due to their use in the cosmetic and food industries, mainly in the production of chocolate. However, the anatomy of their vegetative structures remains poorly studied. The goal of this study was to describe the anatomical features of Theobroma grandiflorum, T. speciosum and T. subincanum to contribute to the biological knowledge of these species, as well as provide support to the biotechnological studies of native fruit plants of the Amazon. Leaves at different developmental stages were collected and analyzed under light microscopy and scanning electron microscopy. Sessile and stalked stellate trichomes and digitiform glandular trichomes were observed in the expanded leaves of T. grandiflorum and T. subincanum. These species were also similar in the morphology of the midrib, the organization of the mesophyll and the presence of starch grains in the midrib pith cells. Claviform glandular trichomes and mucilage cells in the epidermis occurred only in the expanded leaves of T. speciosum. The presence of mucilage secretory trichomes in shoot apices (colleters) of all species is a new finding for the genus Theobroma.